Medical Equipment Procurement Management Strategy Efficiency-Based (Study on the Intensive Care Unit of Pradipa Medika Hospital in Kuningan Regency) - Lulu Rehande Lutfy; Erliany Syaodih; Mira Veranita (Research of Service Administration Health and Sains Healthys, 2025)
Medical equipment procurement is a crucial component in delivering effective and efficient healthcare services. Inadequate planning can lead to budget inefficiencies, service delays, and reduced care quality. This study aims to analyze efficiency-based procurement management strategies to improve hospital service quality. A qualitative descriptive method was employed through in-depth interviews, observations, and documentation involving procurement managers and hospital management. The findings show that efficiency strategies are influenced by need-based planning, value for money budgeting, and transparent supervision. Cross-department collaboration and the use of information systems are also essential for improving procurement effectiveness. This study highlights the need for innovation in procurement management and recommends strengthening governance through internal regulations, enhancing human resource capacity, and utilizing digital technology to support sustainable healthcare services.